2023
DOI: 10.21203/rs.3.rs-2698051/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Unidirectional and Heterogenous Wolbachia Transfer Rates Among Insect Host Orders

Abstract: Background Wolbachia are highly prevalent endosymbiotic bacteria infecting more than two-thirds of arthropods. While Wolbachia are mainly transmitted vertically through the female germline, experiments and phylogenetic studies have suggested that horizontal transmission between hosts is not uncommon. In this study, we aim to get a better understanding of horizontal transfer events between hosts of different orders and between continents using a large database containing nucleotide sequences of the genes wsp … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Although previous research has demonstrated that parasitoids can acquire Wolbachia from their hosts, the reverse direction of transmission, from host to parasitoid, has been largely overlooked and lacks supportive experimental evidence. One possible reason for this oversight is that all parasitoids emerge from their hosts, but hosts are eventually killed by the parasitism of parasitoid wasps ( 17, 23, 24 ). However, parasitoid wasps’ success in parasitizing their hosts does not always reach 100% ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although previous research has demonstrated that parasitoids can acquire Wolbachia from their hosts, the reverse direction of transmission, from host to parasitoid, has been largely overlooked and lacks supportive experimental evidence. One possible reason for this oversight is that all parasitoids emerge from their hosts, but hosts are eventually killed by the parasitism of parasitoid wasps ( 17, 23, 24 ). However, parasitoid wasps’ success in parasitizing their hosts does not always reach 100% ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, it remains uncertain whether Wolbachia can be transferred from parasitoid wasps to their hosts. Some have argued that the transfer of Wolbachia between parasitoid wasps and their hosts is unidirectional, from host to wasp, as all parasitoid wasps emerge from their hosts, but parasitized hosts are eventually killed or castrated if not killed immediately ( 17, 23, 24 ).…”
Section: Introductionmentioning
confidence: 99%